Legality of Iranian Embassy Bombing by Israel in Syria According to International Humanitarian Law - Adeline Anindya Rusdianto; Diajeng Wulan Christianti (Yustisia, 2026)
International Humanitarian Law (IHL) asserts that attacks can only be made against things that help the military and whose destruction gives the military an unambiguous advantage. In April 2024, Israel bombed the Iranian consulate within the embassy premises in Syria, claiming that the building served as a military objective, given Iran's persistent support for Hezbollah in its conflict with Israel and engaged in military activities within the consulate. This paper asserts that the legitimacy of Israel's attack hinges on two critical issues. First, in the ongoing armed conflict between Israel and Hezbollah, to what extent Iran can be legitimately targeted based on its support for Hezbollah. Second, whether Iran's consulate in Syria qualifies as a legitimate target under IHL and whether the attack satisfies the principle of proportionality. This paper concluded that IHL applies to Israel's bombing of the Iranian consulate, and Iran's support of Hezbollah in its conflict with Israel places it at risk of being targeted under IHL. However, this classification does not automatically validate the attack. There is no sufficient evidence to demonstrate that the attack was proportionate, as it targeted an object located in Syria, and the anticipated military advantage fails to justify the civilian casualties incurred.